An unusual elateroid lineage from mid-Cretaceous Burmese amber (Coleoptera: Elateroidea) - Li, Yan-Da; Kundrata, Robin; Packova, Gabriela; Huang, Di-Ying; Cai, Chen-Yang (Scientific reports, 2021)
We here report a new elateroid, Anoeuma lawrencei Li, Kundrata and Cai gen. et sp. nov., from mid-Cretaceous Burmese amber. Though superficially similar to some soft-bodied archostematans, Anoeuma could be firmly placed in the polyphagan superfamily Elateroidea based on the hind wing venation. Detailed morphological comparisons between extant elateroids and the Cretaceous fossils suggest that the unique character combination does not fit with confidence into any existing soft-bodied elateroid group, although some characters indicate possible relationships between Anoeuma and Omalisinae. Our discovery of this new lineage further demonstrates the past diversity and morphological disparity of soft-bodied elateroids.